Food Analysis Laboratory Manual - Nielsen, S. Suzanne; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This second edition laboratory manual was written to accompany Food Analysis, Fourth Edition, ISBN 978-1-4419-1477-4, by the same author. The 21 laboratory exercises in the manual cover 20 of the 32 chapters in the textbook. Many of the laboratory exercises have multiple sections to cover several methods of analysis for a particular food component of characteristic. Most of the laboratory exercises include the following: introduction, reading assignment, objective, principle of method, chemicals, reagents, precautions and waste disposal, supplies, equipment, procedure, data and calculations, questions, and references. This laboratory manual is ideal for the laboratory portion of undergraduate courses in food analysis.
Nutrition Labeling Using a Computer Program -- Assessment of Accuracy and Precision -- Determination of Moisture Content -- Determination of Fat Content -- Protein Nitrogen Determination -- Phenol-Sulfuric Acid Method for Total Carbohydrates -- Vitamin C Determination by Indophenol Method -- Complexometric Determination of Calcium -- Iron Determination in Meat Using Ferrozine Assay -- Sodium Determination Using Ion Selective Electrodes, Mohr Titration, and Test Strips -- Sodium and Potassium Determinations by Atomic Absorption Spectroscopy and Inductively Coupled Plasma-Atomic Emission Spectroscopy -- Standard Solutions and Titratable Acidity -- Fat Characterization -- Fish Muscle Proteins: Extraction, Quantitation, and Electrophoresis -- Enzyme Analysis to Determine Glucose Content -- Gliadin Detection in Food by Immunoassay -- Examination of Foods for Extraneous Materials -- High Performance Liquid Chromatography -- Gas Chromatography -- Viscosity Measurement Using a Brookfield Viscometer -- Calculation of CIE Color Specifications from Reflectance or Transmittance Spectra.
Keywords: Chemistry; Food science; Chemistry; Food Science